In-situ imaging of neutrophil activation in the human alveolar space with neutrophil activation probe and pulmonary optical endomicroscopy. (25th February 2016) - Craven, Thomas; Walton, Tashfeen; Akram, Ahsan; McDonald, Neil; Scholefield, Emma; Walsh, Tim; Haslett, Christopher; Bradley, Mark; Dhaliwal, Kevin
Abstract: Background: Acute respiratory distress syndrome is a severe and heterogeneous condition. Clinical diagnostic criteria lack specificity and fail to differentiate the various inflammatory phenotypes. Diagnosis and stratification can be improved by profiling the neutrophil and one of its enzymes, neutrophil elastase (NE), within the alveolar space. We aimed to combine fibre-based optical endomicroscopy (OEM) with a bespoke imaging probe to deliver a new strategy to elucidate pathobiological processes in the lung. Methods: We designed and synthesised an optical imaging probe termed neutrophil activation probe to fluoresce as it enters the alkaline neutrophilic vacuole and through NE-specific cleavage. Validation was performed with spectrophotometry, confocal microscopy, and flow cytometry. The probe was tested in a perfused large sheep lung model in conjunction with bronchoscopic OEM. Neutrophil activation probe was synthesised to GMP, and a phase 1 study is underway in healthy volunteers and patients in the intensive care unit. The phase 1 study is registered with EudraCT, number 2011-066167-17, and withClinicalTrials.gov, numberNCT01532024 . Findings: Neutrophil activation probe was neutrophil specific, specific to NE among other serine proteinases, and demonstrated dequenching in alkaline pH. Intracellular fluorescence signal determined by flow cytometry increased in chemically activated neutrophils (mean fluorescence index signal increased from 24 144 (SE 6175) to 1·218 × 10 6 (59 325), p<0·0001) within the phagolysosome and was abrogated with chemically induced NE inhibition and phagocytosis inhibition (both p<0·0001), and partly abrogated when alkalisation of the neutrophil vacuole was prevented (p=0·003). Findings were confirmed with bench-top confocal microscopy. Activated neutrophils were detected with OEM in vitro and in the ventilated and perfused sheep lung model. Six healthy volunteers have completed microdosing with neutrophil activation probe and imaging with OEM without any adverse reactions, and without fluorescence signal, thereby validating the specificity of the technique. Interpretation: We have demonstrated the potential utility of this bedside molecular imaging strategy, from bench to patient: the probe functions in a predictable manner, in keeping with its design. A two-site international phase 2 clinical study is planned, which will assess the test characteristics of this novel technique and its ability to predict and stratify clinically important outcomes in a heterogeneous ventilated population in the intensive care unit. Funding: Medical Research Council.